Becoming a person through psychoanalysis - Symington, Neville (Karnac, 2007)
In this book Neville Symington brings together a wide range of lectures and previously published papers along with fresh commentary, providing the reader with a veritable feast of his ideas and further thinking about psychoanalytic theory and clinical practice.